El incumplimiento del derecho constitucional a la no discriminación en los procesos de selección del recurso humano, y la incorporación de reformas al código del trabajo. - González Herrera, Gabriel Alejandro (2013)
The Constitution of the Republic of Ecuador, incorporated as a fundamental principle of equality of all persons before the law, so that everyone, without exception, are protected by the supreme law, to have the same rights, be required to comply with the same obligations and enjoy the same opportunities. In order to ensure this principle, mandate that incorporates all forms of discrimination will be sanctioned by the law Strictly within the workplace, the Constitution of the Republic of Ecuador, prohibited within the processes of recruitment, hiring and employment promotion, apply discriminatory criteria affecting the dignity and integrity of individuals, providing that such processes are underpinned by the need for requirements related to ability, skill, training, merit and ability of the worker. Despite the validity of the above-mentioned constitutional standards within the recruitment process, convened by the Ecuadorian entrepreneurs, you can still demonstrate that such requirements are incorporated requirements that constitute discriminatory criteria such as age, sex, physical presence , among others. Therefore, it affects the validity of constitutional rights, equality and personal integrity, and also the constitutional principle mentioned in the previous paragraph. The lines described above, evidence the existence of a legal issue of constitutional and legal order, which is studied in this work, which has been called: THE CONSTITUTIONAL RIGHT TO BREACH OF NONDISCRIMINATION IN THE SELECTION PROCESS HUMAN RESOURCE, AND THE INCLUSION OF AMENDMENT TO THE CODE OF JOB. Research in formal and structural part is welcomed throughout its development to the rules laid down in the Regulations of the Academic Board of the National University of Loja, and concludes with the approach of a legal proposal to reform the Labour Code, which is oriented to provide a legal solution to the problem studied.